Occurrence of antibiotic resistant Salmonella isolated from dogs in Klang Valley, Malaysia - Abatcha, Mustapha Goni; Zakaria, Zunita; Dhaliwal, Gurmeet Kaur; Thong, Kwai Lin (Malaysian Society for Microbiology, 2014)
Aims: Salmonellosis continues to be a major public health concerned globally. The objective of the study was to determine the occurrence and antimicrobial resistance pattern in Salmonella isolated from non-diarrheic stray and pet dogs in Klang Valley, Malaysia. Methodology and results: A total of 162 dogs were sampled, 15 (9.3%) were positive for Salmonella(stray dogs, n=12; pet dogs, n=3). All the isolates were identified as Salmonella using conventional culture methods and confirmed by PCR-targeting the invA gene. Four different Salmonella serovars were identified upon serotyping including Salmonella Corvallis (53.3%), S.Typhimurium(13.3%), S.Mbandaka(20%), and S. Agona(6.7%). Salmonella isolates were resistant to tetracycline (86.7%), sulphamethazole-trimethoprim (40%), ampicillin (40%), chloramphenicol (33.3%), streptomycin (33.3%), and enrofloxacin (26.7%). None of the isolates was resistant to gentamycin, cephalexin and amoxicillin-clavulanic acid. Eight isolates (53.3%) were multiple drugs resistant. Conclusion, significance and impact study: High number of canine Salmonella isolates developed resistance and this may likely be public health concern.